Hyponatremia: a new predictor of mortality in patients with Shiga toxin-producing Escherichia coli hemolytic uremic syndrome - Alconcher, Laura F. (2018)
(1) Evaluate mortality rate in patients with Shiga toxin-producing Escherichia coli hemolytic uremic syndrome, (2) determine the leading causes of death, and (3) identify predictors of mortality at hospital admission. We conducted a multicentric, observational, retrospective, cross-sectional study. It included patients under 18 years old with Shiga toxin-producing Escherichia coli hemolytic uremic syndrome hospitalized between January 2005 and June 2016. Clinical and laboratory data were obtained from the Argentine National Epidemiological Surveillance System of Hemolytic Uremic Syndrome. Clinical and laboratory variables were compared between deceased and non-deceased patients. Univariate and multivariate analyses were performed. ROC curves and area under the curve were obtained. Seventeen (3.65%) out of the 466 patients died, being central nervous system involvement the main cause of death. Predictors of death were central nervous system involvement, the number of days since the beginning of diarrhea to hospitalization, hyponatremia, high hemoglobin, high leukocyte counts, and low bicarbonate concentration on admission. In the multivariate analysis, central nervous system involvement, sodium concentration, and hemoglobin were independent predictors. The best cut off for sodium was ≤ 128 meq/l and for hemoglobin ≥ 10.8 g/dl. Mortality was low in children with Shiga toxin-producing Escherichia coli hemolytic uremic syndrome, being central nervous system involvement the main cause of death. The best mortality predictors found were central nervous system involvement, hemoglobin, and sodium concentration. Hyponatremia may be a new Shiga toxin-producing Escherichia coli hemolytic uremic syndrome mortality predictor.